1985
DOI: 10.1007/bf00123601
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in a semi-natural Drosophila population after a bottleneck I. Lethals, their allelism and effective population size

Abstract: A semi-natural Drosophila melanogaster population was twice forced through a genetic bottleneck and allowed to recover naturally. In one case additional variation was introduced to the recovering population. The percentage of lethal chromosomes, the level of allelism between these lethals, and the effective population size calculated from the allelism of these lethals all rose sharply in the few generations following each bottleneck, though this was not t~,e case in the very first generation. Thereafter this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…This is an order of magnitude higher than the rate estimated for independently arising lethal genes, which is 0.0041 ± 0.0019 for the O chromosome (Loukas et al 1980) and 0.0029 ± 0.0009 for the second chromosome of D. melanogaster (Begon et al 1985). The lethal genes responsible for the allelism between the Chilean populations analyzed were the lethal genes completely associated with the O 5 inversion, the lethal gene partially associated with the O 3?4?7 arrangement, and a lethal gene found once in both populations and located in an O 3?4?2 chromosome.…”
Section: Gene Flow Between Populationsmentioning
confidence: 64%
See 2 more Smart Citations
“…This is an order of magnitude higher than the rate estimated for independently arising lethal genes, which is 0.0041 ± 0.0019 for the O chromosome (Loukas et al 1980) and 0.0029 ± 0.0009 for the second chromosome of D. melanogaster (Begon et al 1985). The lethal genes responsible for the allelism between the Chilean populations analyzed were the lethal genes completely associated with the O 5 inversion, the lethal gene partially associated with the O 3?4?7 arrangement, and a lethal gene found once in both populations and located in an O 3?4?2 chromosome.…”
Section: Gene Flow Between Populationsmentioning
confidence: 64%
“…Most probably, the linkage disequilibrium for the inversions O 3?4 and O 7 is due to an extreme reduction of crossing over in the region between them (Sperlich and Feuerbach-Mravlag 1974 (Mestres et al 1990(Mestres et al , 1992(Mestres et al , 1995Solé et al 2000) presented only two kinds of allelic (Loukas et al 1980) and in chromosome II of D. melanogaster (p ? = 0.0029) (Begon et al 1985). Overall, out of 99 lethal genes studied in the American continent, 49 proved to be different.…”
Section: Lethal Allelismmentioning
confidence: 94%
See 1 more Smart Citation
“…While demographic methods are frequently used and reasonably robust for a wide range of mating systems and dispersal patterns (Heywood, 1986;Basset et al, 2001), few comparisons of N e involving both demographic and genetic approaches exist (but see Begon et al, 1980;Husband and Barrett, 1992). Husband and Barrett (1992) found that demographic estimates of effective population size were between 2 and 500 times larger than genetic estimates.…”
Section: Effective Size Of Hymenoxys Herbaceamentioning
confidence: 99%
“…The population under study was a Drosophila melanogaster population which occupied a large isolated greenhouse, and has been described in a companion paper (Begon et al, 1984b). The 'prebottleneck' phase of the population lasted from the beginning of the study in October 1979 until 23 April 1980.…”
Section: The Populationmentioning
confidence: 99%